Effect of working gas on physicochemical and biological properties of CaP coatings deposited by RFMS - Kozelskaya A. I. Anna Ivanovna; Fedotkin A. Yu. Aleksandr Yurjevich; Khlusov I. A. Igor Albertovich; Litvinova L. S. Larisa Sergeevna; Tverdokhlebov S. I. Sergei Ivanovich (2021, 2021)
Title screen